PigS and PigP Regulate Prodigiosin Biosynthesis in Serratia via Differential Control of Divergent Operons, Which Include Predicted Transporters of Sulfur-Containing Molecules - Gristwood, Tamzin (American Society for Microbiology (ASM), 2011)
Serratia sp. strain ATCC 39006 produces the red-pigmented antibiotic prodigiosin. Regulation of prodigiosin biosynthesis involves a complex hierarchy, with PigP a master transcriptional regulator of multiple genes involved in prodigiosin production. The focus of this study was a member of the PigP regulon, pigS, which encodes an ArsR/SmtB family transcriptional repressor. Mutations in pigS reduced production of prodigiosin by decreasing the transcription of the biosynthetic operon. The pigS gene is the first in a four-gene operon, which also encodes three membrane proteins (pmpABC) of the COG2391 (DUF395; YedE/YeeE) and COG0730 (DUF81; TauE/SafE) families that we propose constitute transport components for sulfur-containing compounds. We provide the first experimental evidence confirming the membrane localization of a COG2391 protein, that of PmpB. Divergently transcribed from pigS-pmpABC is a bicistronic operon (blhA-orfY), which encodes a metallo-β-lactamase and a coenzyme A-disulfide reductase containing a rhodanese homology domain, both of which may participate in reactions with sulfur-containing compounds. The overproduction of the BlhA and OrfY enzymes and the PmpABC membrane proteins differentially affected pigmentation. We have dissected the contributions of these various proteins and determined their importance in the control of prodigiosin production. PigS-mediated control of prodigiosin occurred via binding directly to a short inverted repeat sequence in the intergenic region overlapping the predicted −10 regions of both pigS and blhA promoters and repressing transcription. PigP was required for the activation of these promoters, but only in the absence of PigS-mediated repression.